Everything is connected: David Jones’s ecopoetry in The Anathemata and ‘The Sleeping Lord’ - Chmielewska, Anita (Studia Anglica Posnaniensia, 2025)
David Jones (1895–1974) is best known for his works on the Great War and the Catholic religion. However, this article explores Jones’s two environmentally focused works and posits that they complement each other, as examples of ecopoetry. Although the term ‘ecopoetry’ did not exist in Jones’s time, he wove ecological issues into his literary works. In his long poem The Anathemata (1952), and in a shorter work entitled ‘The Sleeping Lord’ (1974), Jones explores the idea of a complex microorganism of nature, where environment and culture are two elements indistinguishable from each other. In both texts, the environment is described as a macrostructure on which human civilisation depends. The Anathemata presents the development of the Earth through different geological epochs but focused on the Anthropocene, the human presence, and the impact of civilisation on the planet. This poem emphasises the integration of culture and science into two different but complementary categories. It draws on Aristotelian thought and advocates breaking the artificial division between nature and culture. The Anathemata presents human civilisation as the latest stage of natural development, rather than as a self-contained system. In contrast, ‘The Sleeping Lord’ explores the human impact on the environment, both animate and inanimate, and calls for change to stop detrimental processes triggered by the development of civilisation. Despite the flourishing interest in the modernist explorations of human connections with nature, David Jones remains in the shadow of other modernists. This article aims to draw attention to the ecocritical aspect of his writing.